Electrostimulation of the carotid sinus nerve in mice attenuates inflammation via glucocorticoid receptor on myeloid immune cells - Falvey, Aidan (2020)
Background: The carotid bodies and baroreceptors are sensors capable of detecting various physiological parameters that signal to the brain via the afferent carotid sinus nerve for physiological adjustment by efferent pathways. Because receptors for inflammatory mediators are expressed by these sensors, we and others have hypothesised they could detect changes in pro-inflammatory cytokine blood levels and eventually trigger an anti-inflammatory reflex. Methods: To test this hypothesis, we surgically isolated the carotid sinus nerve and implanted an electrode, which could deliver an electrical stimulation package prior and following a lipopolysaccharide injection. Subsequently, 90 min later, blood was extracted, and cytokine levels were analysed. Results: Here, we found that carotid sinus nerve electrical stimulation inhibited lipopolysaccharide-induced tumour necrosis factor production in both anaesthetised and non-anaesthetised conscious mice. The anti-inflammatory effect of carotid sinus nerve electrical stimulation was so potent that it protected conscious mice from endotoxaemic shock-induced death. In contrast to the mechanisms underlying the well-described vagal anti-inflammatory reflex, this phenomenon does not depend on signalling through the autonomic nervous system. Rather, the inhibition of lipopolysaccharide-induced tumour necrosis factor production by carotid sinus nerve electrical stimulation is abolished by surgical removal of the adrenal glands, by treatment with the glucocorticoid receptor antagonist mifepristone or by genetic inactivation of the glucocorticoid gene in myeloid cells. Further, carotid sinus nerve electrical stimulation increases the spontaneous discharge activity of the hypothalamic paraventricular nucleus leading to enhanced production of corticosterone. Conclusion: Carotid sinus nerve electrostimulation attenuates inflammation and protects against lipopolysaccharide-induced endotoxaemic shock via increased corticosterone acting on the glucocorticoid receptor of myeloid immune cells. These results provide a rationale for the use of carotid sinus nerve electrostimulation as a therapeutic approach for immune-mediated inflammatory diseases.